QUALITATIVE AND QUANTITATIVE ANALYSIS OF FLAVANOIDS OF IMMORTELLA SAMARKAND FLOWERS (HELICHRYSUM SAMARCANDICUM L.) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The paper presents studies of qualitative and quantitative analysis of flavonoids inSamarkand immortelle flowers. The detection of flavonoids was carried out from purified alcoholicextracts using known reactions: cyanidin test, with Wilson's reagent, with a 2% alcohol solutionof aluminum chloride.Methods for determining authenticity and quantitative determination by UV spectrophotometryusing a UV-1800 spectrophotometer (Shimadzu) were studied.
Keywords: samarkand immortelle, flavonoids, spectrophotometry.